Innovative Teaching Strategies for Enhancing Narrative Text Learning in a Sukoharjo High School - Deandra, Chela; Ratih, Koesoemo (Universitas PGRI Adi Buana Surabaya, 2026)
This study aims to gain a comprehensive understanding of the teaching strategies used in teaching English narrative texts at Al Amin alexistoto High School. This study uses a qualitative approach with a case study design at Al Amin High School to examine narrative text teaching strategies. Data were collected through classroom observations and semi-structured interviews with an English teacher and five 12th grade students selected based on their academic achievement levels. Observations were conducted in three sessions to identify teaching strategies, classroom interactions, and student engagement, while interviews aimed to explore the perspectives of teachers and students regarding the learning process. Data were analyzed using Miles and Huberman's interactive model, which includes data reduction, data presentation, and conclusion drawing and verification through triangulation. The results showed that teachers at Al Amin olxtogel High School applied narrative text learning strategies that combined traditional and innovative approaches, with Project-Based Learning (PjBL) as the main strategy supported by visual media such as images and videos. This strategy improves student understanding, participation, and motivation. However, learning still faces obstacles in the form of limited vocabulary, low interest in reading, anxiety about speaking, suboptimal group cooperation, and time management. Overall, the strategies implemented are effective, although there is still a need to develop more varied and interactive methods. However, the implementation still faces several challenges, including limited vocabulary, low reading interest, speaking anxiety, weak group cooperation, and time management issues. These findings imply that although the applied strategies are generally effective, teachers need to develop more varied, interactive, and well-structured learning activities to address students’ language limitations and maximize the effectiveness of narrative text instruction.